3D Finite Element Analysis on Mechanical Behavior of Completion Tubing String for Extra-Deep High Temperature Gas Well. (October 2020) - Liu, Shuang; Shen, Xinpu; Liu, Junyan; Shen, Guoxiao; Xu, Qiang; You, Dongdong
Abstract: 3D Finite Element model was built for analysis of mechanical behavior of tubular system. Factors of wellbore trajectory deviation and frictional contact behavior between tube and casing are considered in the model. Loads of packer setting, hydraulic fracturing, and gas production are included. Numerical solutions of stress and displacement distribution along the tubing are presented. Principal results are: 1) Displacement distribution along the whole length of tubing. 2) Distribution of axial stress and von Mises stress along the whole length of tubing. 3) Distribution of displacement and stress along the tubing section below expansion pipe, as well as frictional contact stress and frictional force in this section.